Portable fingerprint-based attendance recording and monitoring system - Mohd Zin, Mohd Shahril Izuan; Awang Md Isa, Azmi; Mohamad Isa, Mohd Sa'ari (IJCSMC Publishing Team, 2014)
This paper presented the development of a portable attendance monitoring system based on fingerprint identification that can be used by lecturers to monitor attendance of students. Fingerprint-based identification is one of the oldest method among all biometric or security techniques which has been successfully used in numerous applications. Every person has unique, immutable fingerprints. A fingerprint is made of a series of ridges and furrows on the surface of the finger. The distinctiveness of a fingerprint can be determined by the pattern of ridges and furrows as well as the minutiae points. Minutiae points are local ridge characteristics that occur at either a ridge bifurcation or a ridge ending. A portable fingerprint scanner has been utilized as the input to acquire fingerprint images and a laptop equipped with attendance recording and monitoring software as a mobile terminal to process the fingerprint images and record the attendance. This system can be used by lecturers to replace the old method of attendance recording, so that the integrity of the attendance record can be upheld. The actual student’s attendance can be recorded and stored in database. The system is also capable of processing the record to determine students who do not fulfill the attendance percentage requirement.